THE ISSUES OF IMPROVING THE LEGAL ASSURANCE OF GOOD VIRTUE OF SERVICEMEN - Zhukov, S. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The article is dedicated to identifying the essence and ways of improving the good virtue of military officials, state servants and other individuals that are entitled to exercise state functions, in the Ministry of Defense of Ukraine and the Armed Forces of Ukraine.There’re argument provided in favor of the fact that the legal assurance of good virtue of servicemen is presented by a complex of legal acts, ethical codes and principles of their implementation, which in their unity allow to create the ideal model of desirable behavior of military officials, state servants, and other individuals entitled to exercise the function of the state within the Ministry of Defense of Ukraine and the Armed Forces of Ukraine. The peculiarity of the mentioned legal assurance is that the behavioral requirements of the mentioned circles of individuals are not represented in legal acts, but in ethical codes which happen to be a variety of written moral norms. However, the responsibility for violating the prescriptions set by the codes mentioned is not of a moral, but of a judicial category, which is considered to be generally typical for the phenomenon of good virtue in different fields of professional activity.It has been pointed out that the ways and directions for improving the legal assurance of servicemen are to include the corrections stipulated by the Code of virtuous behavior and professional ethics of military officials, state servants and other individuals entitled to exercise the function of the state, in the Ministry of Defense of Ukraine and the Armed Forces of Ukraine, the requirements of behavior of the mentioned individuals are related due to the fact that their duties are included: а) with the determined by the Constitution of Ukraine and approved in the Strategy of national security of Ukraine, approved by the Presidential Decree dated from 14 of September 2020 №392/2020, the priority of protecting the individual, its life and health, honor and dignity, inviolability and security; b) with the adherence to the requirements on access to public information and the application of citizens stipulated by the legislation of Ukraine; c) with the processes of euro-Atlantic integration, that predetermine the necessity to include not only the purely national, but also the generally-accepted criteria on defining good virtue in NATO country members (particularly, The NATO Policy on educating good virtue, approved by the head of states and governments who participated in the Northern Atlantic council in Warsaw on the 8-9 th of July 2016).
Keywords: good virtue, military officials, servicemen, legal norms, moral norms, ethical codes, improvement of legal assurance